Design and Development of Soil Moisture Based Automatic Irrigation System in Nepal - Shiva Kumar Jha; Mita Tarafder; Deepak Dhibar; Bhanu Pokharel; Jiban Shrestha; Keshab Babu Koirala (Newinera Publisher, 2020)
A prototype soil moisture based an automated irrigation system were developed at National Maize Research Program in 2018 to study the water requirement of drought tolerant crop genotype. The irrigation system has been controlled by Arduino UNO as a micro controller. The instant soil moisture data were collected either in Excel format or graphical format using internet of things through the programming of Global System for Mobile Communication: Subscriber Identity Module (GSM:SIM card) of Nepal Telecom. The developed automated irrigation system has found maintained the predetermined threshold soil moisture. This automated irrigation system has been developed to make applicable for drip irrigation system which has operated at low water pressure maintained by 1.5² professional-grade solenoid valve. The introduction of this automated irrigation system has developed the base for Nepalese agricultural scientist in designing and promoting irrigation technology to make Nepalese agricultural more sustainable, mechanized and productive.